Harry Potter and the goblet of fire - Rowling, J. K. (Arthur A. Levine Books, 2000)
Fourteen-year-old Harry Potter joins the Weasleys at the Quidditch World Cup, then enters his fourth year at Hogwarts Academy where he is mysteriously entered in an unusual contest that challenges his wizarding skills, friendships and character, amid signs that an old enemy is growing stronger.